S102 Eosinophil counts as a predictor of future COPD exacerbations in the DYNAGITO trial. (12th November 2019) - Calverley, PMA; Jenkins, C; Wedzicha, JA; de la Hoz, A; Voß, F; Rabe, KF; Anzueto, A
Abstract : Background: There is conflicting evidence from previous studies as to whether eosinophil counts predict the risk of future exacerbations in COPD. Aims: In this post hoc analysis, we investigated the link between baseline eosinophil count and moderate/severe exacerbation rates during the DYNAGITO trial. Methods: DYNAGITO was a 52-week, double-blind, randomised trial in patients with COPD with FEV1 <60% predicted, at least 1 moderate/severe exacerbation in the previous year and no diagnosis of asthma (NCT02296138 ). Exacerbation rates were analysed using a negative binomial model adjusting for prognostic factors such as region and exacerbation history. Results: At baseline, 81% of patients had an eosinophil count ≤300 cells/µL and 49% had an eosinophil count ≤150 cells/µL. 65–76% of patients were receiving ICS across eosinophil subgroups. Similar rates of moderate/severe exacerbations were observed across eosinophil subgroups (figure). Rates were similar across eosinophil counts in patient subgroups with low or high exacerbation history. Conclusions: Relatively few patients had an eosinophil count >300 cells/µL, and there was no increase in exacerbation rates with increasing baseline eosinophil count in the total population, or in patients with low or high exacerbation history. In this population, many of whom were receiving ICS, exacerbation history, but not blood eosinophil count, was an important determinant of exacerbation risk.